PEMBENTUKAN DAN PENDAMPINGAN KELOMPOK PEMBUDIDAYA IKAN (POKDAKAN) UNTUK PENGUATAN EKONOMI MASYARAKAT DESA SUMBEREJO KABUPATEN SITUBONDO JAWA TIMUR - Ach. Khumaidi; Abdul Muqsith; Abdul Wafi; Musyaffa Rafiqie; Dimas Galang Prakosa; Ach. Dhofyun Nufur; Moh. Shahibussa’ Dayki (As-Sidanah, 2024)
In order to strengthen the economy of the community in Sumberejo Village and overcome the limited stock to supply catfish, it is necessary to form a community business, namely a catfish cultivator group. There were twelve potential community members were gathered to be taught and assisted in the process of establishing and managing a catfish cultivation business. The members of the community were taught technically how to cultivate catfish right through to the marketing process, then facilitated the formation of farmer groups together with the Situbondo district fisheries instructor and the Sumberejo Village Head until the "Santri Aquaculture Ibrahimy" farmer group was formed. Assistance is provided starting from the process of building a pond, preparing the pond, keeping fish and harvesting, to the marketing process. The results of economic benefits began to be seen in the first harvest cycle, there was a profit of IDR 2,400,000, with capital issued of IDR 7,000,000,-. With the existence of the Santri Aquaculture Ibrahimy farmer group, it can be achieved at least to overcome the shortage of daily consumptive stock of catfish and to strengthen the village economy by opening up employment opportunities for the people of Sumberejo Village.